Tensioning of the radioscaphocapitate and long radio-lunate ligaments for dynamic radiocarpal instability. (May 2018) - Rubensson, Carin; Johansson, Torsten; Adolfsson, Lars
During 1994–2003, we treated 20 patients with post-traumatic radial-sided wrist pain and dynamic radiocarpal instability. After arthroscopy confirmed no disruption of the radioscaphocapitate ligament and an increased laxity of the ligament, we passed a strip of the radioscaphocapitate ligament through the long radio-lunate ligament. The rationale of this procedure was to increase tension of the two ligaments and to close the space of Poirier. Eighteen patients were assessed after 1–3.7 years (mean 2.5 years). Four patients were symptom-free and 11 patients were markedly improved. Fourteen patients were followed for 11–15 years; four patients were symptom-free and eight patients were markedly improved. Two reported unchanged symptoms and none was worse in the follow-up. Based on our findings, we suggest a cause of post-traumatic radial-sided wrist pain is laxity of the radiocarpal joint. We conclude that our surgical procedure increases tension in the radioscaphocapitate and long radio-lunate ligaments and decreases wrist pain at rest and during activity. Level of Evidence: IV